2016
DOI: 10.1534/genetics.116.187922
|View full text |Cite
|
Sign up to set email alerts
|

Production of Small Noncoding RNAs from the flamenco Locus Is Regulated by the gypsy Retrotransposon of Drosophila melanogaster

Abstract: Protective mechanisms based on RNA silencing directed against the propagation of transposable elements are highly conserved in eukaryotes. The control of transposable elements is mediated by small noncoding RNAs, which derive from transposonrich heterochromatic regions that function as small RNA-generating loci. These clusters are transcribed and the precursor transcripts are processed to generate Piwi-interacting RNAs (piRNAs) and endogenous small interfering RNAs (endo-siRNAs), which silence transposable ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
(70 reference statements)
2
20
0
Order By: Relevance
“…With this aim, we analyzed the mortality rate of Lam 4643/K2 mutant flies carrying a gypsy insertion in the cut locus (ct A allele). This gypsy insertion was isolated among flam A individuals, and the resulting mutant has the same genetic background as the original flam A strain [31]. We found that the ct A allele in heterozygous condition slightly but significantly increases mortality ( Figure 1, compare column 5 with 7), while in homozygous condition it greatly increases the mortality rate of the pharate (Figure 1, column 10).…”
Section: Pharate Mortality Induced By Lam Loss-of-function Mutations mentioning
confidence: 80%
See 3 more Smart Citations
“…With this aim, we analyzed the mortality rate of Lam 4643/K2 mutant flies carrying a gypsy insertion in the cut locus (ct A allele). This gypsy insertion was isolated among flam A individuals, and the resulting mutant has the same genetic background as the original flam A strain [31]. We found that the ct A allele in heterozygous condition slightly but significantly increases mortality ( Figure 1, compare column 5 with 7), while in homozygous condition it greatly increases the mortality rate of the pharate (Figure 1, column 10).…”
Section: Pharate Mortality Induced By Lam Loss-of-function Mutations mentioning
confidence: 80%
“…However, we considered the possibility that this phenotype could depend on the genetic background. In a previous report, we showed that pharate mortality during the eclosion process can be induced by euchromatic insertions of the gypsy retrotransposon in genetic backgrounds that are permissive for gypsy transposition [31]. To test a possible involvement of gypsy, the X chromosomes of the original Lam 4643/K2 flies, derived from the wild type Canton S strain, were replaced with the X chromosome carrying flam A , a permissive allele of flamenco.…”
Section: Pharate Mortality Induced By Lam Loss-of-function Mutations mentioning
confidence: 99%
See 2 more Smart Citations
“…piRNA clusters are dynamic components of the Drosophila melanogaster genome and their structural composition has been linked to differential regulatory abilities. For instance, the ability of the D. melanogaster master piRNA locus flamenco to control transposons such as gypsy , ZAM and /defix was shown to be dependent on frequent chromosomal rearrangements, loss or gain of fragmented TE sequences (Zanni et al 2013; Guida et al 2016). Additionally, variations in the composition of subtelomeric piRNA clusters were observed upon adaptation to laboratory conditions of D. melanogaster wild collected flies (Asif-Laidin et al 2017).…”
Section: Introductionmentioning
confidence: 99%